RANCANGAN MISI LAPSAT-2 FM - Adrianti P.S.; Prabowo, Gunawan S; Mukhtar, Andi; Nasser, Eriko; Mukhayadi, M. (BRIN Publishing, 2003)
Now adays, itis widelly used the term Nano-satellite when we refer to those satellites whose mass less than about 10 kg. The design of LAPSAT-2 FM has weight more than 10 kg and less then of 15 kg but we consider as a nano-satellite continuing the previous design LAPSAT-1, This satellite designed as technology demonstrator, carrying store-and forward communication and remote sensing missions. Satellite build together with Malaysia in a same mission in parallel separately. This paper, discussed about mission definition and analysis referring to orbit, payload, budget and launch alternative and also mission operation.